Porous silicon covalently-grafted with chloro-styrenic carbons for fast Li+ diffusion and durable lithium-storage capability - Tran, Minh Xuan; Nguyen, Thuy-An; Lee, Joong Kee; Lee, Sang-Wha (Elsevier BV, 2023)
Silicon-based anode materials have critical issues such as drastic volume changes, huge stress generation, and the thickening of solid-electrolyte interphase layer. Thus, a new strategy for improving silicon interface is necessary for significantly enhanced Li+ ion transportation and structural stability during prolonged cycling, while simultaneously reducing severe side reactions. Herein, we prepared porous silicon particles covalently linked with styrene-based polymers (polystyrene (PS) and poly(4-chlorostyrene) (PCS)) via a facile non-atmospheric thermolytic process at a low-temperature (<= 400 degrees C), in which the decomposed styrenic carbon fragments are covalently grafted on the silicon surface via Si-O-C and Si-C species. Notably, PCS-grafted porous silicon exhibited the significantly enhanced electrochemical performance (i.e., a high rate capability of 1270 mAh g-1 at 20 A g-1, 90.7% of initial capacity at 4 A g-1, and a reversible capacity of 1725 mAh g-1 after 200 cycles), because of the dual covalent linkages of Si-C and Si-O-C species in chloro-styrenic carbons that provide durable lithium storage capability and fast Li+ transportation. Specifically, the Si-C linkage enforced the formation of a durable interlayer that protects the Si active material from reactive electrolytes, and the polarized Si-O-C linkage facilitates the rapid transport of Li+ ions.